2021
DOI: 10.3390/cancers13092045
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Stem Cells with Differentiation Agents as an Alternative to Genotoxic Chemotherapy for the Treatment of Malignant Testicular Germ Cell Tumors

Abstract: Testicular germ cell tumors (TGCTs) are exceptionally sensitive to genotoxic chemotherapy, resulting in a high cure rate for the young men presenting with these malignancies. However, this treatment is associated with significant toxicity, and a subset of malignant TGCTs demonstrate chemoresistance. Mixed nonseminomas often contain pluripotent embryonal carcinoma (EC) cells, the cancer stem cells (CSCs) of these tumors. We hypothesized that differentiation therapy, a treatment strategy which aims to induce dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…ECs represent the totipotent stem cell population of these tumors able to further differentiate into YST, Ter and Cc. [ 5 , 6 ]. Both sub-entities, seminomas and non-seminomas, arise from primordial germ cells (PGCs) which are developmentally arrested and eventually turn into the precursor lesion termed germ cell neoplasia in situ (GCNIS) [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECs represent the totipotent stem cell population of these tumors able to further differentiate into YST, Ter and Cc. [ 5 , 6 ]. Both sub-entities, seminomas and non-seminomas, arise from primordial germ cells (PGCs) which are developmentally arrested and eventually turn into the precursor lesion termed germ cell neoplasia in situ (GCNIS) [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 TR or SAL treatment induces changes in EC cell morphology from an ES cell-like to a fibroblast-like state, accompanied by a loss of pluripotency marker expression and a loss of tumorigenic potential. 28 To determine if miR-290-295 cluster miRNAs were expressed by mouse EC cells, we analyzed the expression of miRNAs from this family in the EC cell lines and differentiated counterparts. In particular, levels of miR-291a-3p (homologous to human miR-372-3p and 373-3p) and miR-292-3p and miR-293 (homologous to different isoforms of human miR-371a-3p) were measured as representative miRNAs in this cluster and collectively referred to as miR-291-293 hereafter (Supplemental Figure 1).…”
Section: Cultured Murine Ec Cells Express and Secrete Mir-291-293 And...mentioning
confidence: 99%
“…It is also worth noting that there are 2 anti-depressants present in our results, Venlafaxine and Nefazodone. These results are particularly interesting as it has recently been shown that psychiatric drugs offer potential as anti-cancer therapeutics (Loehr et al, 2021). Moreover, a recent review has specifically addressed the need to investigate psychiatric drugs for treatment of gastrointestinal cancers (Avendaño-Félix et al, 2020).…”
Section: Anastrozolementioning
confidence: 99%